2012
DOI: 10.3892/mmr.2012.1154
|View full text |Cite
|
Sign up to set email alerts
|

Expression of ghrelin and leptin during the development of type 2 diabetes mellitus in a rat model

Abstract: The aim of this study was to investigate the syste-matic changes in ghrelin and leptin expression, as well as their correlation with insulin resistance (IR) during the development of type 2 diabetes mellitus (T2DM) in a rat model. T2DM was induced in rats fed a high-fat (HF)-diet followed by the intraperitoneal injection of low-dose streptozotocin (STZ, 35 mg/kg). Sixty male Sprague-Dawley rats were divided into 4 groups: the control, HF-4W (HF diet for 4 weeks), HF-8W (HF diet for 8 weeks) and the T2DM group.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 33 publications
2
17
0
1
Order By: Relevance
“…Increased serum levels of ghrelin are also contrary to the increased levels of insulin, leptin and resistin we found, as previous reports indicate ghrelin reduces insulin secretion and is negatively correlated with leptin and resistin [47], [48], [49], [50]. However, it is important to consider that the assay we used in this study measured total ghrelin and not only the active acylated form of this gastric peptide hormone [51].…”
Section: Discussionsupporting
confidence: 53%
“…Increased serum levels of ghrelin are also contrary to the increased levels of insulin, leptin and resistin we found, as previous reports indicate ghrelin reduces insulin secretion and is negatively correlated with leptin and resistin [47], [48], [49], [50]. However, it is important to consider that the assay we used in this study measured total ghrelin and not only the active acylated form of this gastric peptide hormone [51].…”
Section: Discussionsupporting
confidence: 53%
“…There are many studies on the effect of diabetes on serum and tissue levels of ghrelin [15,37]. STZ-induced rats were found to have significantly higher serum ghrelin levels.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes mellitus is a serious and complex metabolic disease that affects the health of individuals worldwide (1). Numerous studies have demonstrated that diabetes mellitus is associated with, and induces, certain cardiovascular diseases (2).…”
Section: Introductionmentioning
confidence: 99%